Diagnosing Femoroacetabular Impingement From Plain Radiographs: Do Radiologists and Orthopaedic Surgeons Differ?. Issue 7 (21st July 2014) - Ayeni, Olufemi R.; Chan, Kevin; Whelan, Daniel B.; Gandhi, Rajiv; Williams, Dale; Harish, Srinivasan; Choudur, Hema; Chiavaras, Mary M.; Karlsson, Jon; Bhandari, Mohit
Background: A diagnosis of femoroacetabular impingement (FAI) requires careful history and physical examination, as well as an accurate and reliable radiologic evaluation using plain radiographs as a screening modality. Radiographic markers in the diagnosis of FAI are numerous and not fully validated. In particular, reliability in their assessment across health care providers is unclear. Purpose: To determine inter- and intraobserver reliability between orthopaedic surgeons and musculoskeletal radiologists. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Six physicians (3 orthopaedic surgeons, 3 musculoskeletal radiologists) independently evaluated a broad spectrum of FAI pathologies across 51 hip radiographs on 2 occasions separated by at least 4 weeks. Reviewers used 8 common criteria to diagnose FAI, including (1) pistol-grip deformity, (2) size of alpha angle, (3) femoral head-neck offset, (4) posterior wall sign abnormality, (5) ischial spine sign abnormality, (6) coxa profunda abnormality, (7) crossover sign abnormality, and (8) acetabular protrusion. Agreement was calculated using the intraclass correlation coefficient (ICC). Results: When establishing an FAI diagnosis, there was poor interobserver reliability between the surgeons and radiologists (ICC batch 1 = 0.33; ICC batch 2 = 0.15). In contrast, there was higher interobserver reliability within each specialty, ranging from fair to good (surgeons: ICC batch 1 = 0.72; ICC batch 2 = 0.70 vs radiologists: ICC batch 1 = 0.59; ICC batch 2 = 0.74). Orthopaedic surgeons had the highest interobserver reliability when identifying pistol-grip deformities (ICC = 0.81) or abnormal alpha angles (ICC = 0.81). Similarly, radiologists had the highest agreement for detecting pistol-grip deformities (ICC = 0.75). Conclusion: These results suggest that surgeons and radiologists agree among themselves, but there is a need to improve the reliability of radiographic interpretations for FAI between the 2 specialties. The observed degree of low reliability may ultimately lead to missed, delayed, or inappropriate treatments for patients with symptomatic FAI.